Potential contribution of nanotechnology to the circular economy of plastic materials - Distaso, Monica (Acta Innovations, 2020)
The problem of plastic accumulation in the environment requires the development of effective strategies to shift the paradigm of used plastics from wastes to resources. In the present contribution, after an overview of the current plastic management strategies, the possible role of nanotechnology to this emerging field is considered. In particular, the challenges related to the use of nano-additives to improve the properties of recycled plastics is discussed based on the fundamental aspects of colloid stabilisation. Finally, the contribution of nanotechnology to the fabrication of effective catalysts for the depolymerisation of plastics into the constituent monomers is outlined.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Inorganic pigments; Nanocomposites; Nanoparticles; Packaging; Polymers